Determination of Medical Faculty Clinical Students' Attitudes Towards Patient Safety: A Mixed Design Study - Yasemin Güner; Kübra Yilmaz; Dilan Yurtseven; Tuğçe Mümin (Elsevier, 2024)
Background: The study was planned to determine the attitudes of medical faculty students in clinics toward patient safety. Methods: It is a mixed-design study using quantitative and qualitative methods. The "student information form" and the "Attitudes toward Patient Safety Culture Questionnaire (APSQ)" created using "Google Forms" were e-mailed to clinical students of the medical faculty. Quantitative data were collected from 125 students. Then, semi-structured focus group interviews were conducted with six students from each class. The data were obtained through video and audio recordings of the 45-minute interviews through the Zoom program. Results: According to the results, 86% of the 125 students did not receive any training on patient safety. The total score of the students on the APSQ was 94.87 ± 14.32. Six main themes and twenty sub-themes emerged from the qualitative data. The main themes are students' awareness of patient safety, students' misconceptions about "patient safety," students' knowledge about the scope of patient safety, students' experiences with medical errors, deficiencies in educational processes on patient safety, and suggestions for educational approaches to patient safety. Conclusions: After completing undergraduate medical education, physicians typically assume roles as general practitioners in various healthcare settings, such as hospital's emergency departments, home care, or community health centers. The lack of awareness among medical students about patient safety is a significant concern that needs to be addressed. As stakeholders in their education, students recognize the importance of being well-prepared to provide safe and effective patient care in their future roles as physicians.